Improvement in the electrochemical performance of LiNi0.8Co0.1Mn0.1O2 cathode material by Li2ZrO3 coating - Liang, Hongmei; Wang, Zhixing; Guo, Huajun; Wang, Jiexi; Leng, Jin (Applied surface science, 2017)
[Display omitted] •A lithium ionic conductor, Li2ZrO3, is coated on LiNi0.8Co0.1Mn0.1O2.•The coating process is carried on the precursor which is more close the practical production.•Cycling performance and rate capability of LiNi0.8Co0.1Mn0.1O2 has been improved by Li2ZrO3 coating.•The mechanism of modification is explored by various means of characterization. Li2ZrO3 with three dimensional tunnels for Li+ diffusion is introduced to improve the electrochemical performance of LiNi0.8Co0.1Mn0.1O2. The coating process is carried on the precursor rather than on the product. The Li2ZrO3 coating layer with thickness of 10nm has been detected by morphological observation. Electrochemical tests indicate that the Li2ZrO3-coating samples display better electrochemical performance than the bare sample. Especially, the 2% Li2ZrO3 coated sample delivers desirable capacity retention of 94.5% after 200 cycles at 1C, which is superior to the bare one (82.5%). Furthermore, the 1% Li2ZrO3 coated sample exhibits superior specific capacity of 144.3mAhg−1 at 10C, much greater than the bare sample (107.4mAhg−1). The cyclic voltammograms and electrochemical impedance spectra tests demonstrate that the Li2ZrO3-coated layer can cut down the electrochemical polarization of the materials and decrease the charge-transfer resistance in the cycling process. The XRD patterns and SEM images of the electrodes before and after 200 cycles reveal the Li2ZrO3-coated samples have more stable structure during cycling.